1978
DOI: 10.1128/aac.13.2.277
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Experimental Murine Cryptococcosis: a Comparison of Miconazole and Amphotericin B

Abstract: Miconazole was compared with amphotericin B in the treatment of murine cryptococcosis. Both subcutaneous and intraperitoneal administration of miconazole produced serum levels higher than the minimum inhibitory concentration for the challenge strain. However, maximal tolerable doses of miconazole gave no increase in survival. When combined with amphotericin B, miconazole demonstrated neither additive nor antagonistic effects on survival. Spleen and brain counts of cryptococci were not lowered by miconazole; al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Figure 3 This course of a total of 30 mg of amphotericin B per kg was highly effective in that it caused all mice to survive for more than 3 months after challenge, when they were sacrificed. Prior studies with normal BALB/c mice similarly treated had produced similar results and also had shown markedly reduced, sometimes undetectable, spleen and brain cryptococcal counts immediately after completion of their treatment (14). Thus, we considered that these amphotericin Btreated nu/X, thymus-containing mice were probably "cured" of their cryptococcosis.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Figure 3 This course of a total of 30 mg of amphotericin B per kg was highly effective in that it caused all mice to survive for more than 3 months after challenge, when they were sacrificed. Prior studies with normal BALB/c mice similarly treated had produced similar results and also had shown markedly reduced, sometimes undetectable, spleen and brain cryptococcal counts immediately after completion of their treatment (14). Thus, we considered that these amphotericin Btreated nu/X, thymus-containing mice were probably "cured" of their cryptococcosis.…”
Section: Resultsmentioning
confidence: 66%
“…This is consistent with the serum levels in both VOL. 14,1978 on May 7, 2018 by guest http://aac.asm.org/ Downloaded from nu/nu and nu/X mouse sera being close to the minimum inhibitory concentration for amphotericin B at 24 h after the dose. A second study, in which serum was obtained 6 h after the dose, showed similar growth rates in control sera inoculated with 104 C. neoformans.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…In contrast, in a discovery study of multiple formulations, a 3-day delay in therapy ( Fig. 1B) resulted in reduced efficacy of all drugs tested, allowing discrimination of median survivals between the fungistatic drug fluconazole (53 days, P Ͻ 0.002 versus untreated), monotherapy with 5FC (47 days, P Ͻ 0.002 versus untreated), and a high-dose amphotericin B regimen previously described to be effective in a mouse model (10) in combination with 5FC (11). Using this model, CAmB at 5 mg/kg/day i.p.…”
Section: Resultsmentioning
confidence: 87%
“…In these studies, multiple formulations of CAmB were evaluated to test which compound and route of administration were most efficient against C. neoformans in mice. A delayed-treatment model that results in more rapid failure of fungistatic drugs such as fluconazole than of fungicidal amphotericin B was also utilized (10).…”
mentioning
confidence: 99%